Bioefficacy of imidacloprid 17.8 SL against whitefly, Bemisia tabaci (Gennadius) in brinjal (The Journal of Plant Protection Sciences, 2023)
Field experiments were conducted in two crop seasons during 2010 and 2011 with brinjal (var Muktakeshi) to  evaluate the efficacy of chloro-neonicotinoid as foliar application against whitefly, Bemisia tabaci (Gennadius).  Imidacloprid 17.8 SL @ 50 g a.i./ha, was found superior against whiteflies among other treatments, received low est number of whitefly population (1.55/plant) and offered maximum reduction of whiteflies (83.15%) as well as  highest marketable fruit yield (146.50 q/ha). However, imidacloprid at lower doses showed nearly similar results.  The other neonicotinoid, thiamethoxam also provided similar levels of protection as that of imidacloprid. The con ventional insecticide, methyl demeton (125 g a.i./ha) was less effective.
Keywords: Brinjal; neonicotinoids; whitefly